Thermal reduction to control the spacing in graphene oxide membranes: effect on ion diffusion and electrical conduction. Issue 74 (22nd July 2016) - Alhadhrami, A.; Salgado, S.; Maheshwari, V.
Abstract : Inter-layer spacing in reduced graphene-oxide membranes which modulates their ion-diffusion electrical and electrochemical characteristics is controlled by temperature of thermal reduction. Abstract : Means to control the inter-layer spacing in graphene oxide and reduced graphene oxide membranes is required to tailor their properties. We report that based on the temperature of thermal reduction the interlayer spacing in these membranes can be controlled from 7.6 Å to 4.6 Å. This is the critical range that matches with the hydrated ionic radii of commonly found ions in water and hence is useful to tailor the diffusion characteristics of these membranes. In accordance with the change in inter-layer spacing, both the in-plane and out-of-plane electrical conductivity of the membranes also increases and this is also observed in the electrochemical characteristics of the membranes.